2021
DOI: 10.3389/fpsyg.2021.706495
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of the Health Behavior Motivation Scale

Abstract: The article presents the construction and validation process of the Health Behavior Motivation Scale (HBMS), which measures the motivation toward pro-health behaviors in population of healthy adults. The tool is conceptually based on Self-Determination Theory (SDT) and more precisely on one of its subtheories—Organismic Integration Theory (OIT). In the first stage of the construction, the linguistic validation with competent judges procedure allowed to eliminate the items which were not correctly formulated. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Having been subjected to linguistic and cultural adaptations, the Chinese variant of HBMS proves more fitting for the distinct situations and cultural milieu within the Chinese context and thus offers a more accurate depiction of the motivational landscape with respect to health behaviors among the Chinese population. The Chinese version of the HBMS includes important factors such as self-regulation ability, along with both internal and external drivers ( Poraj-Weder et al, 2021 ). As a result, it can reveal the source of motivation for people to engage in healthy behaviors with greater accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having been subjected to linguistic and cultural adaptations, the Chinese variant of HBMS proves more fitting for the distinct situations and cultural milieu within the Chinese context and thus offers a more accurate depiction of the motivational landscape with respect to health behaviors among the Chinese population. The Chinese version of the HBMS includes important factors such as self-regulation ability, along with both internal and external drivers ( Poraj-Weder et al, 2021 ). As a result, it can reveal the source of motivation for people to engage in healthy behaviors with greater accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The Health Behavior Motivation Scale (HBMS), which comprises a total of 5 dimensions and 30 entries, was created in 2011 by Professor Magdalena Poraj-Weder and coworkers ( Poraj-Weder et al, 2021 ). It has been demonstrated that this scale, which is used to measure healthy people’s motivation to undertake pro-health behaviors in Poland, has good psychometric qualities.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth and final step was allocated to selecting the number of constructs for the rotated solution, emphasizing interpretability. This decision-making process was guided by the a priori conceptual framework of the study, the Eigenvalues computed in the second step, and the relative interpretability of the rotated solution computed in the third step [59,60]. Consequently, the constructs of the final version of the EMM-FC scale were compiled and named in accordance with the outcomes of the EFA.…”
Section: Discussionmentioning
confidence: 99%
“…The internal structure of the EMM-FC scale in the cross-sectional study was verified using EFA [59,60]. The calculations were performed, allowing the development of a stable and theoretically valid five-factorial measurement model that described the regulatory styles included in the motivational continuum by Ryan and Deci [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the use of MD-omega, though sound from a methodological point of view [ 41 ], is not frequent in validations of health behaviour scales. The few instrument development studies in which MD-omega was computed either do not report MD-omega total or values for all factors [ 46 , 47 ]. The overall internal consistency of the new HBS-16 as measured by Cronbach’s alpha, was very good and similar to other health behaviour measures [ 23 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%